Kelompok Milenial dan Tantangan Pembangunan Kota: Gentrifikasi dan Komersialisasi Ruang di Kota Yogyakarta - Imron Amrozi; Dicky Riandy Prasetya Sultansyah; Afifatul Millah Nurul Aulia Hidayat; Amalinda Savirani (Jurnal Studi Pemuda, 2021)
This study aims to explore gentrification in the city of Yogyakarta through the production and commercial- ization process of tourism space, explore the impact of gentrification felt by local communities in a cross-gen- erational context, and formulate strategies that millennials can do to support housing access in the city of Yogyakarta. Through the research process in Sosrokusuman Village located in the Malioboro area, this study finds that the transformation of settlements in Sosrokusuman cannot be separated from its territory within the Malioboro area as a tourism space. In addition, the exploration on the impact of gentrification for local com- munities shows that the scarcity of housing due to land conversion (commercialization) and high land prices have caused millennials with salaries equivalent to the regional minimum wage to have difficulty accessing housing in Sosrokusuman and have the potential for voluntary eviction. Meanwhile, the exploration of strat- egies that can be done to support housing access for millennials is through cross-sector collaboration with the concept of collaborative implementation program (CIP).